2022
DOI: 10.3389/fpubh.2022.1008028
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of birth defects in teenage pregnancies: Based on provincial surveillance system in eastern China

Abstract: BackgroundHealthcare for adolescents and birth defects (BD) prevention are highlighted public health issues. The epidemiology of birth defects in teenage pregnancies has not been studied extensively.ObjectivesTo investigate the prevalence trend and spectrum of BDs among teenage mothers.MethodsThis observational study covered all births registered in the BD surveillance system in Zhejiang Province, China, during 2012–2018. The annual change in the prevalence of BDs among adolescent mothers was estimated. Crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Epidemiological surveys show a brief increase in the incidence of gastroschisis in North and South America and many European countries ( 29 ). There are still few studies on gastroschisis in China, and in 2022, a study on the incidence in the Chinese population showed that the incidence of gastroschisis in the offspring of patients under 20 years of age was 10.62 per 10,000 live births; however, the incidence of gastroschisis in the offspring of parents between the ages of 25 and 29 years was 1.51 per 10,000 live births ( 11 ). The same findings suggest that the offspring of pregnant adolescents are at high risk of gastroschisis ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological surveys show a brief increase in the incidence of gastroschisis in North and South America and many European countries ( 29 ). There are still few studies on gastroschisis in China, and in 2022, a study on the incidence in the Chinese population showed that the incidence of gastroschisis in the offspring of patients under 20 years of age was 10.62 per 10,000 live births; however, the incidence of gastroschisis in the offspring of parents between the ages of 25 and 29 years was 1.51 per 10,000 live births ( 11 ). The same findings suggest that the offspring of pregnant adolescents are at high risk of gastroschisis ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on birth defects in the Chinese population, the incidence of gastroschisis in the offspring of patients under 20 years of age was 10.62 per 10,000 live births; however, the incidence of gastroschisis in the offspring of parents between the ages of 25 and 29 years was 1.51 per 10,000 live births ( 11 ). Additionally, the prevalence of gastroschisis has increased, from 3.6 per 10,000 live births in 1995–2005 to 4.9 per 10,000 live births in 2006–2012 ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Congenital anomalies not only seriously affect the survival and quality of life of children but also cause great pain and heavy economic burden on families and society ( Boyd et al, 2008 ; Heaney, Tomlinson & Aventin, 2022 ). Owing to environmental pollution, deficiencies in maternal nutrition, radiation exposure, poor lifestyle habits, and advanced maternal age, China has a high incidence of birth defects ( Chen et al, 2022 ; Ghazi et al, 2021 ; Tan, Sethi & Sulaiman, 2022 ; Zhang et al, 2020 ) of approximately 5.6%, equivalent to approximately 900,000 new birth defects every year ( Li & Di, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sufficiency during pregnancy is important for normal fetal development [ 18 ]. Folate deficiency is associated with adverse outcomes including maternal anemia, neural tube defects, and birth defects [ 19 , 20 ]. However, because folic acid in natural foods is easily broken down during cooking and processing, the amount of folic acid alone is insufficient for pregnant women due to this loss.…”
Section: Introductionmentioning
confidence: 99%